2017
DOI: 10.1002/hfm.20697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a semiautomatic protocol using plastering and three‐dimensional scanning techniques with the direct measurement protocol for hand anthropometry

Abstract: This study aimed to compare a three‐dimensional (3D) semiautomatic measurement protocol (3D‐SAMP) that measures hand dimensions using a plaster hand and a 3D scanner with the conventional direct measurement protocol (DMP). An experiment was conducted to measure 52 dimensions of one hand by 20 measurers with three repetitions. The locations of landmarks attached to the plaster hand were automatically identified and then measurements of the hand dimensions were automatically extracted in the 3D‐SAMP. Significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The maximum AE obtained with Gemini structured-light scanning was 0.94 mm. This finding is comparable with the results of other studies on the accuracy of structured-light scanning applications 27 , and other imaging applications used for obtaining measurements of the hand 1,28 . Although the Gemini structured-light scanning system has not been employed for the clinical measurement of hand, the results of our study are encouraging.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The maximum AE obtained with Gemini structured-light scanning was 0.94 mm. This finding is comparable with the results of other studies on the accuracy of structured-light scanning applications 27 , and other imaging applications used for obtaining measurements of the hand 1,28 . Although the Gemini structured-light scanning system has not been employed for the clinical measurement of hand, the results of our study are encouraging.…”
Section: Discussionsupporting
confidence: 90%
“…Continuous improvement in technology and software has made it possible for researchers and clinicians to achieve realistic 3D imaging, although it may never be fully attainable. Furthermore, Lee et al reported that subjective satisfaction achieved with the 3D semiautomatic measurement protocol (3D-SAMP) with respect to ease of hand measurement was significantly greater than that achieved for the direct measurement protocol 28 . This made the 3D-SAMP more preferable to direct measurement because of the shorter interaction time with the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, various decision tools utilize only operational data while making decisions. Such methods can only obtain knowledge of operational aspects (Hu et al, 2016;Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%